An Aesthetical and Ethical Reading of Heidegger’s The Question Concerning Technology - García Sánchez, Rafael (2024)
Modern technology is a product of modern subjectivity and, more concretely, of a conception of metaphysics grounded on the apotheosis of the subject-object relation. The fact is that this conception of technology is out of control and, thus unleashed, it declares its radical independence. Technology, emancipated and proclaimed absolute rhýler, encloses our society. In this context, the will is deprived of all extra-technical means capable of safeguarding reality, voraciously abused and exposed to the danger of being reduced to mere replaceable utility, existence or resource. The out-of-tune world in which we live does not show itself in the truth of its being, but in the mere utility of a service that it must provide. On this path, it reaches human beings themselves, who with supreme discretion have been reduced to mere human resources.